Learning Mathematical Literacy Across Islands in an Archipelagic Country Through Cross-Cultural STEM Trails - Cahyono, Adi Nur; Sukestiyarno, Yulius Leonardus; Kharisudin, Iqbal; Iqbal, Muhammad; Zulkardi; Safrudiannur; Lavicza, Zsolt; Miftahudin (Mathematics Education Journal, 2025)
This study explored a program aimed at designing cross-cultural STEM trails in three regions of an archipelagic country to enhance students' mathematical literacy. The research employed an exploratory mixed-methods design, involving 30 prospective teachers, in-service teachers, and lecturers and 50 students. Data were collected through observations, interviews, documentation, and mathematical literacy tests. They were analyzed using qualitative coding/triangulation and ANOVA. The study took place in three cities located on different islands during the 2024 academic year. The study began with implementation of a teacher training program to equip them with the necessary skills to design STEM Trails using the stemtrails.id platform. This application was developed in previous research. The trails were designed to integrate STEM contexts, cultural themes, and landmark elements in three Indonesian cities. Students used the trails to learn mathematical literacy and gain insight into the cultures of other regions. The location of tasks and trails in remote areas prompted task authors to innovate task design using technologies such as 3D printing. This technology facilitates student exploration, as with general math trails, but also incorporates miniature object models relevant to the tasks. The teacher selected project-based learning as an appropriate model for this strategy. The results demonstrated measurable improvements in mathematical literacy, with average post-test scores rising from M = 68.4 (SD = 9.3) to M = 81.7 (SD = 8.6), t(142) = 9.21, p < .001. Cross-island cultural triangulation fostered collaborative learning across geographically separated regions, thereby demonstrating a strategy for overcoming archipelagic barriers. The model can be expanded to other regions through digital integration and culturally grounded STEM task design. In this way, it can offer a pathway for nationwide application.